HUBUNGAN ANTARA PERSEPSI SISWA TERHADAP KETERAMPILAN GURU DALAM MENGAJAR DENGAN TINGKAT MINAT BELAJAR SISWA PADA PELAJARAN MATEMATIKA - FATMAWATI, NENIY (Universitas Muhammadiyah Gresik, 2015)
Interest held by the student learning can not be separated from the school as a learning environment factors, as interest related to the satisfaction of the students to the school. Hurlock (1999: 141-142) suggests that there are various ways in which children show their attitude toward school when the school they see as the disadvantages.The purpose of this study was to determine whether or not the relationship between students' perception of teachers in teaching skills to the level of student interest in math. This questionnaire using Likert scale with response options as well as a score that has four answer choices, namely SS (very appropriate), S (fit), TS (not fit), and STS (strongly disagree).Data from both variables treated with Spearman Rank correlation technique with a significance level of 5%. The results showed that the magnitude of the correlation coefficient betweenvariable students' perception of teacher skills in teaching (X) with a variable level of student interest in math (Y) is generated,r = 0.942, p = 0.000, significant level of p <0.05, df = n and - 2 = 84 -2 = 82 by testing two-way tables may be obtained price r = 0.212. These results illustrate that the count r> r table (0.942> 0.212), then Ho is rejected and Ha accepted otherwise.So it can be concluded that there is a significant relationship between students' perception of teacher skills in teachingwith the level of student interest in mathematics lessons to students of SMP Negeri 2 Manyar Gresik.The coefficient of determination (r2) of r = 0.9422 = 0.887. That is, r2 = 0.887 (89%) informed that the contribution of students' perception of teacher skills in teaching with the level of student interest in math by 89%. While the remaining 11% is influenced by other variables not examined.